Proximal and Distal Parts of Sweetpotato Adventitious Roots Display Differences in Root Architecture, Lignin, and Starch Metabolism and Their Developmental Fates - Singh, Vikram; Zemach, Hanita; Shabtai, Sara; Aloni, Roni; Yang, Jun; Zhang, Peng; Sergeeva, Lidiya; Ligterink, Wilco; Firon, Nurit (Frontiers in Plant Science, 2021)
Sweetpotato is an important food crop globally, serving as a rich source of carbohydrates, vitamins, fiber and micronutrients. Sweetpotato yield depends on the modification of adventitious roots into storage-roots. The underlying mechanism of this developmental switch is not fully understood. Interestingly, storage-root formation is manifested by formation of starch-accumulating parenchyma cells and bulking of the distal part of the root, while the proximal part does not show bulking. This system, where two parts of the same adventitious root display different developmental fates, was used by us in order to better characterize the anatomical, physiological and molecular mechanisms involved in sweetpotato storage-root formation. We show that, as early as one and two weeks after planting, the proximal part of the root exhibited enhanced xylem development together with increased/massive lignin deposition, while, at the same time, the distal root part exhibited significantly elevated starch accumulation. In accordance with these developmental differences, the proximal root part exhibited upregulated transcript levels of sweetpotato orthologues of Arabidopsis vascular-development-regulators and key genes of lignin-biosynthesis, while the distal part showed upregulation of genes encoding enzymes of starch-biosynthesis. All these recorded differences between proximal and distal root parts were further enhanced at five weeks after planting, when storage-roots were formed at the distal part. Our results point to down-regulation of fiber formation and lignification, together with upregulation of starch biosynthesis, as the main events underlying storage-root formation, marking/highlighting several genes as potential regulators, providing a valuable database of genes for further research.